Serum evaluation of leptin, IL-6, IGF-1 and estrogen in obese bitches with early stages of mammary carcinoma - S.V. Teixeira; I.L.D. Silva; F.C. Nunes; C.B. Campos; M.R. Oliveira; G.E. Lavalle; G.D. Cassali (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to relate the serum concentration IL-6, IGF-1, leptin and estrogen in non-castrated bitches with or without overweight and early stage mammary carcinomas. Forty-three bitches were divided into four groups, two groups without mammary carcinomas with and without overweight, and two groups with mammary carcinomas with and without overweight. Overweight bitches, with or without mammary carcinomas, were statistically different from bitches by ideal weight, in relation to ECC, IMCC and body fat percentages (P< 0.0001). There was a positive correlation between ECC and IMCC (P< 0.0001), ECC and % GC (P< 0.0001), and IMCC and % GC (P< 0.0001). A positive correlation was found between serum leptin and IL-6 (P= 0.0451) and leptin and IGF-1 (P= 0.05). A positive correlation (P= 0.0053) between ECC and leptin was found in the analysis of body evaluation methods and serum concentrations, and a negative correlation between ECC and IL-6 (P= 0.0435). Among the fat percentage and the leptin concentration, there was a positive correlation (P= 0.0016), as found between the IMCC and leptin (P= 0, 0209). In this study, no association was observed between excessive weight and the presence of early stage mammary carcinomas.